ANALISIS PERSEPSI KUALITAS PERKULIAHAN DI LABORATORIUM PERKANTORA DAN SEKRETARI PROGRAM PENDIDIKAN VOKASI UNIVERSITAS INDONESIA - Istiadi, Istiadi; Ridha, Mohammad (Jurnal Vokasi Indonesia, 2016)
Laboratory of the study Program is the on factor that imfluence the quality of student in the process of their study in Vocational Program . In order that, laboratory must become the crucial factor in producing qualified alumni. The quality of teaching ini laboratory in general was imfluenced some factors like: lecturer/instructur, curicullum, tools or su pported facilities in laboratory. For that reason, in this research we want to know the general of student in laboratory teaching. Factors that was identified included : degree of student satisfaction, quality of teaching, and laboratory supporting facilities . Output of this research is benefited as the input in developing the ideal office and Secretary Laboratory that sincronized with student needs.